Reduced-intensity delayed intensification in standard-risk pediatric acute lymphoblastic leukemia defined by undetectable minimal residual disease: results of an international randomized trial (AIEOP-BFM ALL 2000) - Schrappe, Martin; Bartram, Claus R. (Journal of clinical oncology, 2018)
PurposeDelayed intensification (DI) is an integral part of treatment of childhood acute lymphoblastic leukemia (ALL), but it is associated with relevant toxicity. Therefore, standard-risk patients of trial AIEOP-BFM ALL 2000 (Combination Chemotherapy Based on Risk of Relapse in Treating Young Patients With ALL) were investigated with the specific aim to reduce treatment intensity.Patients and MethodsBetween July 2000 and July 2006, 1,164 patients (1 to 17 years of age) with standard-risk ALL (defined as the absence of high-risk cytogenetics and undetectable minimal residual disease on days 33 and 78) were randomly assigned to either experimental reduced-intensity DI (protocol III; P-III) or standard DI (protocol II; P-II). Cumulative drug doses of P-III were reduced by 30% for dexamethasone and 50% for vincristine, doxorubicin, and cyclophosphamide, which shortened the treatment duration from 49 to 29 days. The study aimed at noninferiority of reduced-intensity P-III; analyses were performed according to treatment given.ResultsFor P-III and P-II, respectively, the 8-year rate of disease-free survival (± SE) was 89.2 ± 1.3% and 92.3 ± 1.2% (P = .04); cumulative incidence of relapse, 8.7 ± 1.2% and 6.4 ± 1.1% (P = .09); and overall survival, 96.1 ± 0.8% and 98.0 ± 0.6% (P = .06). Patients with ETV6-RUNX1-positive ALL and patients 1 to 6 years of age performed equally well in both arms. The incidence of death during remission was comparable, which indicates equivalent toxicity. The 8-year cumulative incidence rate of secondary malignancies was 1.3 ± 0.5% and 0.6 ± 0.4% for P-III and P-II, respectively (P = .37).ConclusionAlthough the criteria used for the standard-risk definition in this trial identified patients with exceptionally good prognosis, reduction of chemotherapy was not successful mainly because of an increased rate of relapse. The data suggest that treatment reduction is feasible in specific subgroups, which underlines the biologic heterogeneity of this cohort selected according to treatment response.
Published at jco.orgon November 17, 2017
Gesehen am 23.04.2020